G05 Do lower limb kinetic and kinematic differences in drop jump landings persist when players have returned to sport following knee ligamentous injuries? - Cannon-Noren, Harry; Page, Richard (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Knee injuries (KI) are identified as one of the most burdensome lower limb injuries in football with long and complicated rehabilitation and high re-injury risk. Current research often describes technique deficits being present upon RTS, often being a result of poor return to sport (RTS) testing procedures. More recently, research has advocated the use of single leg vertical jump assessments, due to the specificity of the movement to injury mechanisms and the ability to consider different phases of the task to inform practitioners of joint contributions to the propulsion and landing phases. The aim of this research is to identify whether these functional deficits exist 12-24 months post RTS authorisation, to help inform future RTS in applied practice. Twenty-four semi-professional male footballers (mean ± SD: age 25 ± 4 years; stature 182 ± 7 cm; body mass 80 ± 8 kg) were recruited into a previously injured and a control group. Participants completed 5 repetitions of single leg drop jump (SLDJ). Jump height, ground contact time, reactive strength index, peak moments, angles and power contributions for the hip, knee and ankle were measured using Qualisys Track Manager then exported to Visual 3D. This study was approved by the Edge Hill University Ethics Committee. No significant findings were identified for landing one however, during the propulsion phase there was a difference between groups (P = 0.026, d=1.14) for knee flexion at take-off. Most differences were identified during landing two bilaterally in both groups. Within the injured group, differences were identified for peak hip (P = 0.011, d = 0.028) and knee powers (P < 0.001, d = 1.269), hip (P < 0.001, d = 1.924) and knee power contribution % (P < 0.001, d = 1.269). No differences were identified for the performance measures or through performing statistical parametric mapping for hip and knee powers for all three phases. Joint coupling analysis was conducted for the total ground contact time amalgamating the landing and propulsion phase, this was analysed as Hip-Knee, Hip-Ankle and Knee-Ankle, with significant findings in Hip-Knee and Hip-ankle. Both groups elicited bilateral differences however, no differences between the injured limb and dominant control limb were identified. To better apply this form of analysis to RTS testing, functional movements such should be undertaken when athletes are injury free to provide baseline measurements to refer to if undertaking rehabilitation from KI. Likewise, the current study identified that joint contributions could be identified in a more applied setting using the range of motion data from each joint.